Postdeposition Annealing Effect on Cu2ZnSnS4 Thin Films Grown at Different Substrate Temperature. (29th April 2014) - Nadi, Samia Ahmed; Chelvanathan, Puvaneswaran; Zakaria, Zaihasraf; Alam, Mohammad Mezbaul; Alothman, Zeid A.; Sopian, Kamaruzzaman; Amin, Nowshad
Abstract : Cu2 ZnSnS4 (CZTS) thin films were deposited on top of Molybdenum (Mo) coated soda lime glass (SLG) substrates using a single target rf magnetron sputtering technique. The sputtering parameters such as base pressure, working pressure, rf power, argon (Ar) gas flow rate, and deposition time were kept consistent throughout the experiment. The effect of different substrate temperatures, for example, room temperature (RT), 300°C, 350°C, 370°C, 400°C, and 450°C, was analyzed by studying their structural, electrical, and optical properties. As-sputtered films were then annealed at 460°C. X-ray diffraction (XRD) measurement revealed the structure to be kesterite with peak of (112) plane in both annealed and as-sputtered CZTS thin films. The crystallinity of the films improved with the increasing substrate temperature until 370°C. Secondary phases of MoS2, Cu x MoS x, Cu x SnS x, Cu x S, and Cu6 MoSnS8 (hemusite) were also observed in the annealed CZTS films. Scanning electron microscopy (SEM) shows crystallite size of deposited CZTS thin film to be proportionally related to deposition temperature. The highest surface roughness of 67.318 nm is observed by atomic force microscopy (AFM). The conductivity type of the films was found to be p-type by Hall effect measurement system.